A Cu‐Doping Strategy to Enhance Photoelectric Performance of Self‐Powered Hole‐Conductor‐Free Perovskite Photodetector for Optical Communication Applications. Issue 8 (18th June 2020) - Liu, Zhiyong; Liu, Xingyue; Sun, Bo; Tan, Xianhua; Ye, Haibo; Zhou, Jianxin; Tang, Zirong; Shi, Tielin; Liao, Guanglan
Abstract: Photodetectors are essential parts of wireless optical communication system for obtaining high fidelity signal transmission, which mainly relies on expensive and energy‐consuming Si, GaN, and InGaAs based photodiodes. The emerging organic–inorganic metal halide perovskite materials, with the merits of low‐cost, strong optical absorption, superior charge transport, and so on, are widely investigated in photodetection applications. Herein, a Cu ion induced p‐type doping strategy for perovskite film is proposed to facilitate hole transport, passivate trap states, avoid charge accumulation, and suppress recombination of photogenerated carriers, contributing to an enhanced photoelectric performance for self‐powered hole‐conductor‐free devices. The optimal device shows a highest responsivity of 0.37 A W −1, detectivity of 1.06 × 10 12 Jones, linear dynamic range of over 101 dB, and an ultimate photoresponse rate approaching 5 µs. Moreover, an optical communication system integrated with the perovskite photodetector as light signal receiver for transmitting digital signals is demonstrated, in which characters can be transmitted accurately, and audio signal is recovered with high fidelity. The results suggest that with proper chemical modification, perovskite materials are promising alternative to inorganic semiconductors for efficient photodetection in advanced integrated optical communication system. Abstract : A Cu ion induced p‐type doping strategy is proposed to enhance photoelectric performance of self‐powered hole‐conductor‐free perovskite photodetector. The device shows an excellent responsivity of 0.37 A W −1, detectivity of 1.06 × 10 12 Jones, linear dynamic range of over 101 dB, and photoresponse rate approaching 5 µs, making it perform well in optical communication system for transmitting text and audio signals.